Symptoms and needs of patients with advanced lung cancer: early prevalence assessment - Kuon, Jonas; Vogt, Jeannette; Mehnert, Anja; Alt-Epping, Bernd; van Oorschot, Birgitt; Sistermanns, Jochen; Ahlborn, Miriam; Ritterbusch, Ulrike; Stevens, Susanne; Kahl, Christoph; Ruellan, Anne; Matthias, Kathrin; et al. (Oncology research and treatment, 2019)
Background: Little is known on symptom burden, psychosocial needs, and perception of prognosis in advanced lung cancer patients at the time of diagnosis, although early assessment is strongly recommended within the setting of daily routine care. Methods: Twelve study sites cross-sectionally assessed symptoms and psychosocial needs of patients suffering from newly diagnosed incurable lung cancer. Assessment comprised NCCN distress thermometer, FACT-L, SEIQoL-Q, PHQ-4, and shortened and modified SCNS-SF-34 questionnaires. Additional prognostic information from both patients and physicians were collected. Results: A total of 208 patients were evaluated. Mean age was 63.6 years, 58% were male, 84% suffered from stage IV lung cancer, and 71% had an ECOG performance status of 0-1. Mean distress level was 5.4 (SD 2.5), FACT-L total score was 86 (21.5), and TOI 50.5 (14.9). PHQ-4 was 4.6 (3.3), and shortened and modified SCNS-SF-34 showed 9 (8.7) unmet needs per patient. According to their physicians’ perspective, 98.1% of patients were reflecting on and 85.2% were accepting incurability, while 26.5% of patients considered the treatment to be of curative intent. Conclusion: Our findings emphasize substantial domains of symptom burden seen in newly diagnosed, incurable lung cancer patients. Oncologists should be aware of these features and address prognostic issues early in the disease trajectory to facilitate opportunities to improve coping, advance care planning, and appropriate integration of palliative care, thus improving quality of life.